Photosensitive automated doors to exclude small nocturnal predators from nest boxes. (16th December 2018) - Stojanovic, D.; Eyles, S.; Cook, H.; Alves, F.; Webb, M.; Heinsohn, R.
Abstract: Nest boxes are a crucial tool for wildlife conservation. Although boxes are often safer from predators than natural nests, if predator and prey are of similar body size survival in boxes may become unacceptably low. Protecting boxes from small predators may be critical to the aims of a project, but no available tools can be reliably deployed for long periods in the field. We trial automated light sensitive mechanical doors on nest boxes to protect birds nesting in boxes from a small nocturnal predator. At three sites we deployed arrays of nest boxes, and fitted a subset (treatment group) with automated doors, while others were left unprotected. Box occupancy by the target species, clutch size and nest fate (successful/failed) were monitored using motion activated cameras and by manual checking. Birds in nest boxes fitted with automated doors had a significantly lower risk of nest failure 0.25 (±0.11se ) compared to 0.81 (± 0.07se ) in the control group. No nests in the treatment group failed due to predation, whereas all nest failures in the control group were attributable to predation. The treatment group did not differ significantly from controls in clutch size. Automated doors operated for a 3 month breeding season reliably, with minimal maintenance (but battery charge should be monitored). We provide a useful new tool for protecting nest boxes from nocturnal predators, and automated doors did not have any deleterious reproductive consequences on the nests they protected. The automated doors offer practical conservation solutions for nest box conservation programs that (1) are conducted in remote locations with limited accessibility, (2) require protection measures to be deployed for long periods, (3) minimize behavioural/physiological impacts on target species, (4) require targeted protection against nocturnal predators against which more conventional approaches are ineffective or inappropriate. Abstract : Nest boxes are important for conservation and research, but can be vulnerable to small‐bodied predators. We develop and test an automated door to exclude nocturnal predators from boxes. Birds nesting in boxes fitted with automated doors had higher survival than controls and the doors operated reliably over several months in a field setting. Our new tool will help overcome the risks of predation in nest boxes in habitats where small predators occur.